Mapping UI/UX Evaluation Methods, Evaluation Objects, and Measured Aspects in Comparative Studies: A Systematic Literature Review - Bachtiar Mujaddidi; Berlilana Berlilana; Purwadi Purwadi (Jambura Journal of Electrical and Electronics Engineering, 2026)
— UI/UX evaluation is a crucial aspect in ensuring the quality of interaction between users and systems, particularly in the context of increasingly complex digital applications. However, the wide variety of available evaluation methods often leads to differences in results and interpretations when assessing system performance and user satisfaction. This study aims to review and compare UI/UX evaluation approaches used in comparative studies. Unlike previous review studies that mainly focused on specific application domains, user perceptions, or technological trends, this study specifically maps the relationship between UI/UX evaluation methods, evaluated objects, and user experience dimensions measured in comparative studies. The method employed is a systematic literature review (SLR) following the PRISMA guidelines. Literature was retrieved from the Scopus database, and through the selection process, 13 articles met the inclusion criteria. The analysis revealed that UI/UX evaluation approaches in comparative studies are predominantly focused on comparing interaction techniques or interaction approaches, accounting for 61.5% (8 articles) of the selected studies. This is followed by comparisons of software performance, which represent 23.1% (3 articles), and comparisons of evaluation methods, which account for 15.4% (2 articles). Evaluations generally employ a combination of performance metrics, user perception measures, and additional experiential indicators such as cognitive workload and physiological responses. The findings show that each method or system demonstrates strengths in specific evaluation dimensions, highlighting the need for a multidimensional and multi-method evaluation approach to obtain a more comprehensive understanding of UI/UX. The main contribution of this study is the development of a systematic synthesis that links evaluation methods, evaluation objects, and UI/UX indicators employed in comparative studies. The findings provide a broader understanding of current evaluation practices and may serve as a reference for researchers and practitioners in designing more appropriate and consistent UI/UX evaluation strategies.